(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Sufism is a mystic body of religious practice found in Islam which is characterized by a focus on Islamic purification, spirituality, ritualism, asceticism and esotericism. Sufism is a path of spiritual advancements cum expansion of consciousness leading to awareness of self in the universe. The practice of Sufism leads to the development of innate spiritual and initiative abilities. Ancient Kashmir has been a practical place of stay and meditation for the saints, Sufis, Rishis and other devoted worshipers of Allah. The philosophy spread along the valley after the arrival of Sufis from central Asia. As necessitated by love’s jealousy, the Sufi is taken away from all except the Truth. One of the most important doctrines of Sufism is the concept of the "Perfect Man" al-Insan al- Kamil. This doctrine states that there will always exist upon the earth a "Qutb" - a man who is the perfect channel of grace from God to man and in a state of wilaya sanctity, being under the protection of God. This paper is an attempt to understand the Short Biography of Sufi saint, Hazrat Abdul Qadir Jeelani (R.A)